A NEW RECTANGULAR FINITE ELEMENT FOR PLANE ELASTICITY ANALYSIS - admin, M.T.BELARBI 1; KHELASSI, A. (Courrier du Savoir; Vol. 6 (2005): Courrier du Savoir, 2014)
ABSTRACT A simple rectangular element having 2d.o.f/node at each node is developed. This element is based on the strain approach. From some numerical examples, by using the concept of static condensation it is concluded that the exact solutions can be obtained. This element is nonconforming but satisfies the patch test and produces results which are acceptable within practical engineering accuracy even when few elements are employed.